The Effect Of Size, Roa, And Leverage On Tax Avoidance On Property & Real Estate Companies Listed On The Indonesia Stock Exchange For The 2018-2020 Period - Imam Hidayat; Pika Prawesty (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study is to identify and analyze the effect of Tax Avoidance on Size, ROA and Leverage on sector property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. The population used in this study were all companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. Sampling techniques in this study used purposive sampling methods, and samples in this study as many as 10 companies. The data analysis method used in this study with the Eviews program version 12. The results of this study showed that Size, ROA and Leverage have a positive effect on Tax Avoidance